2020
DOI: 10.2337/figshare.12357506.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Association Between HbA1c and Time in Hypoglycemia During CGM and Self-Monitoring of Blood Glucose in People With Type 1 Diabetes and Multiple Daily Insulin Injections: A Randomized Clinical Trial (GOLD-4)

Abstract: <b><i>Objective: </i></b>According to recent guidelines, individuals with type 1 diabetes should spend less than 4.0% per day with glucose levels <3.9 mmol/L (<70 mg/dL) and less than 1.0% per day <3.0 mmol/L (<54 mg/dL). <p><b><i><br> Research methods: </i></b>In the GOLD randomised cross-over trial, 161 individuals with type 1 diabetes treated with multiple daily insulin injections (MDI) were randomised to Continuous Glucose Monitoring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…This indicates that the wisdom of attempting TIR > 70% should always be evaluated on the background of achieved GMI or mean glucose and TBR. 20 We found a curvilinear relation between TIR and GMI and recognize a similar result from a pediatric population. Mean glucose is calculated from all values (both scanned and imported every 15 min), from AUC divided by the time period, and from mean of 15 min average.…”
Section: Discussionsupporting
confidence: 86%
“…This indicates that the wisdom of attempting TIR > 70% should always be evaluated on the background of achieved GMI or mean glucose and TBR. 20 We found a curvilinear relation between TIR and GMI and recognize a similar result from a pediatric population. Mean glucose is calculated from all values (both scanned and imported every 15 min), from AUC divided by the time period, and from mean of 15 min average.…”
Section: Discussionsupporting
confidence: 86%
“…In a post-hoc analysis, within the CGM group, the largest HbA 1c reductions were achieved for patients with the highest baseline HbA 1c levels (!9.0%) [28]. Also, results from both the DIAMOND and GOLD studies showed that CGM use was associated with a significantly reduced time spent inand episodes ofhypoglycaemia, particularly overnight [29,30].…”
Section: Intermittent Cgm (Flash Glucose Monitoring)mentioning
confidence: 96%
“…Real-time CGM. There is a strong evidence base showing the benefits of real-time CGM in people with diabetes receiving insulin, including the DIAMOND T1D/T2D and GOLD T1D studies [27][28][29][30][31][32]. In both the DIAMOND and GOLD studies, HbA 1c levels were significantly reduced with real-time CGM versus SMBG [31,32].…”
Section: Intermittent Cgm (Flash Glucose Monitoring)mentioning
confidence: 99%
“…Continuous glucose monitoring (CGM) and continuous subcutaneous insulin infusion (CSII) are two diabetes technologies that have revolutionized diabetes care, with both technologies associated with improved HbA1c levels, increased TIR, and fewer hypoglycemic events compared with MDI [23][24][25][26][27][28].…”
Section: Continuous Glucose Monitoring and Subcutaneous Insulin Infusionmentioning
confidence: 99%